A novel prognostic gene set for colon adenocarcinoma relative to the tumor microenvironment, chemotherapy, and immune therapy - Zhou, Hui; Wang, Yongxiang; Zhang, Zijian; Xiong, Li; Liu, Zhongtao; Wen, Yu (Frontiers in Genetics, 2023)
Colon adenocarcinoma (COAD) is a common, aggressive, malignant tumor. Heterogeneity in the tumorigenesis and therapy response leads to an unsatisfactory overall survival of COAD patients. Our study aimed to identify tools for a better prediction of COAD prognosis, bolstering the development of better-personalized treatment and management. We used the Least Absolute Shrinkage and Selection Operator (LASSO) Cox model to analyze the prognosis-related gene datasets from Gene Expression Omnibus (GEO) and verified them using the Cancer Genome Atlas (TCGA) database. The area under the curve (AUC) was calculated using the subject operating characteristic curve (ROC) to evaluate the predictive ability of the risk score model. Gene Set Enrichment Analysis (GSEA) was used to identify the significantly enriched and depleted biological processes. The dysfunction and exclusion (TIDE) algorithm was taken to explore the relationship between risk score and immunotherapy. The observations collectively helped us to construct a nomogram to predict prognosis. Finally, the correlation between drug sensitivity and prognostic gene sets was conducted based on the Cancer Therapeutics Response Portal (CTRP) analyses.We constructed a scoring model, to assess the significance of the prognosis risk-related gene signatures, which was relative to common tumor characteristics and tumor mutational burden. Patients with high-risk score had higher tumor stage and poor prognosis (P<0.05). Besides, the expressions of these genes were in correlation to changes in the tumor microenvironment (TME). The accuracy of the novel nomogram model with a risk score and TNM-stage predict prognosis in predicting prognosis was higher than the accuracy of the TNM stage. Further analysis showed that high-risk score was associated with tumor immune rejection. Patients with low-risk score have a better prognosis with chemotherapy than those with high-risk score. Compared with patients in the high-risk group, patients in the low-risk group had a significant survival advantage after receiving chemotherapy. In addition, the prognostic gene sets aid the assessment of drug sensitivity.This study establishes a new prognostic model to better predict the clinical outcome and TME characteristics of COAD. We believe, our model also serves as a useful clinical tool to strengthen the functioning of chemotherapy, immunotherapy, and targeted drugs.